Survival in adenosquamous cancer of the lung: Is it really so unfavorable? - (:unkn) unknown (Baycinar Medical Publishing, 2015)
Background: This single-center study aims to investigate whether a significant difference exits between the survival rates of patients operated for adenosquamous cancer of the lung (ASCL) and patients operated for adenocarcinoma or squamous cell carcinoma. Methods: A total of 2,203 patients (1,977 males, 226 females; mean age 57.8±34.9 years; range 22 to 86 years) operated for non-small cell lung cancer in our hospital between January 2002 and January 2011 were retrospectively analyzed for pathological diagnosis, survival, and tumor staging. Results: As a result of pathological analysis, the diagnosis of adenosquamous cancer was confirmed in 46 out of 2,203 (2.1%) patients. The median survival time was 53.6 months (range 21.1 to 68.2 months) for adenocarcinoma, 48.1 months (range 24.4 to 66.9 months) for squamous cell cancer, and 27.9 months (range 10.7 to 44.6 months) for ASCL (p=0.026). The median survival time was 21.6 months in the group of patients with predominating adenocarcinoma, 21.4 months in the group of patients with predominating squamous cell carcinoma, and 37.8 months in the group of patients with codominant cell lines (p=0.007). Conclusion: In our study, the survival rate of ASCL patients was lower than that of patients with squamous cell carcinoma or adenocarcinoma. Further clinical studies are needed to investigate whether adjuvant chemoradiotherapy following surgical resection improves overall survival rates.
Keywords: Adenosquamous cancer; Lung cancer; Surgical resection; Survival time